THE INFLUENCE OF KOREN’S CELEBRITY ENDORSEMENT AND YOUTH BUYING BEHAVIOR ON YOUTH APPAREL PURCHASE DECISION IN MANADO - Andries, Alfa Loudy (Jurnal EMBA: Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2014)
Korean Pop culture was affecting many countries. Indonesia was shipped impact is mainly due to the deployment of Indonesian culture which is a developing country that is easily influenced by the developed countries. The change of how youth in Manado response to Korean?s celebrity appearance need to investigate. This research designed to find out the influence of Korean?s celebrity endorsement  and youth buying behavior on youth apparel purchase decision in Manado. The method used to analyze the data is the Multiple Regression Analysis which enables the researcher to analyze the influence of the independent variables to the dependent variable, which is Youth Apparel Purchase Decision. The independent variables in this research are Korean?s Celebrity Endorsement and Youth Buying Behavior. While the samples of respondent?s size are 100 respondents who dressed like Korean celebrity. The result of this research shows that there is significant simultaneous and partial influence of Korean?s celebrity endorsement and youth buying behavior on youth apparel purchase decision in Manado. Therefore, to enhance the influence on youth apparel purchase decision in Manado these two proponents should be considered intensively. Keyword: Korean?s celebrity endorsement, youth buying behavior